Menganalisis Alih Kode Dan Campur Kode Bahasa Pada Video Channel Youtube Detik.Com Yang Berjudul Impersonation Game With Iqbaal Ramadhan - Siti Roro Zahro (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
This study aims to describe the form and type of code switching and language code mixing on Detik.com YouTube Channel video entitled Impersonation game with Iqbaal Ramadhan. I conducted this analysis accompanied by a comparison with 4 scientific journals that were the subject of study. This research uses a qualitative approach and the method used in this study is a descriptive method. In this study, data collection techniques were used with free listening techniques, proficient libas and recording techniques. The data is taken from a video show on Detik.com's YouTube Channel entitled Impersonation game with Iqbaal Ramadhan. The results of the analysis of research data that have been stated in the previous discussion, it can be concluded that the form of code switching and code mixing is often used by Iqbaal Ramadhan in the video. Iqbaal Ramadan often switches from Indonesian to foreign languages and regional languages and vice versa. The form of code transfer found by researchers in the field, namely the form of internal code transfer which occurs, the transition from Indonesian, to regional languages or vice versa, while the code mixing that occurs, namely the mixing or insertion of regional language words into Indonesian conversation, either intentionally or unintentionally. The form of mixed code obtained by the researcher, which is in the form of mixed code into mixing Indonesian with foreign languages and regional languages (Tae). This happened because of Iqbaal Ramadan's habit of using multilingual languages, so that code switching and code mixing in conversations in the surrounding environment occurred.